Empowering Micro, Small, and Medium Enterprises through Education on the Utilization of QRIS as a Digital Transaction Alternative - Triansyah, Fadli Agus; Thania, Andi Cici; Ritonga, Marito; Lubis, Nela Permata Sari; Tharifah, Nabila Tijani; Balqis, Sakina; Yaqin, Muh Ainul (Pena Dimas: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to enhance the digital financial literacy of Micro, small, and medium-sized businesses (MSMEs) can learn how to use the Indonesian Standard Quick Response Code (QRIS) as a different way to pay online. The program activities involved culinary, service, and retail practitioners from MSMEs, as claimed by the State University of Medan. These activities were differentiated and grouped into planning, socialization and education, technical training and simulation, mentoring and monitoring, and evaluation, within the framework of the Participatory Action Research (PAR) approach. This approach helps MSME practitioners who need assistance to learn and practice digital transactions, as well as reflect on their experiences afterwards. There are positive results related to participants' knowledge, confidence, and technical competence in using QRIS. Moreover, the program fostered behavioral change and collaboration among MSME actors in adopting digital transaction systems. The implementation of QRIS also contributed to more efficient, secure, and transparent financial management within their businesses. Overall, this community service initiative demonstrates that participatory and practice-based education combined with continuous mentoring is an effective strategy to accelerate digital transformation and promote financial inclusion among MSMEs. This initiative is also closely aligned with the United Nations Sustainable Development Goals (SDGs), particularly Goal 8: Decent Work and Economic Growth, Goal 9: Industry, Innovation, and Infrastructure, and Goal 10: Reduced Inequalities. By improving digital financial literacy and promoting inclusive access to digital payment systems, the program supports the creation of a more resilient, innovative, and equitable economic ecosystem for MSMEs in Indonesia.